The evaluation of benefit of newly prepared reversible inhibitors of acetylcholinesterase and commonly used pyridostigmine as pharmacological pretreatment of soman-poisoned mice - Kassa, Jiří; Korábečný, Jan; Nepovímová, Eugenie (Acta Medica, 2017)
AIM: The ability of four newly prepared reversible inhibitors of acetylcholinesterase (6-chlorotacrine, 7-phenoxytacrine, compounds 1 and 2) and currently used carbamate pyridostigmine to increase the resistance of mice against soman and the efficacy of antidotal treatment of soman-poisoned mice was evaluated. METHODS: The evaluation of the effect of pharmacological pretreatment is based on the identification of changes of soman-induced toxicity that was evaluated by the assessment of its LD50 value and its 95% confidence limit using probitlogarithmical analysis of death occurring within 24 h after administration of soman. RESULTS: 6-chlorotacrine was only able to markedly protect mice against acute toxicity of soman. In addition, the pharmacological pretreatment with 6-chlorotacrine or compound 2 was able to increase the efficacy of antidotal treatment (the oxime HI-6 in combination with atropine) of soman-poisoned mice. The other newly prepared reversible inhibitors of acetylcholinesterase (7-phenoxytacrine, compound 1) as well as commonly used pyridostigmine did not influence the efficacy of antidotal treatment. CONCLUSION: These findings demonstrate that pharmacological pretreatment of somanpoisoned mice can be promising and useful in the case of administration of 6-chlorotacrine and partly compound 2.
Keywords: Isoquinolines; Animals; Pyridinium Compounds; pyridinové sloučeniny; lidé; Mice; myši; isochinoliny; Pyridostigmine Bromide; Male; pyridostigmin-bromid; Soman; kombinovaná farmakoterapie; soman; zvířata; mužské pohlaví; cholinesterasové inhibitory; Cholinesterase Inhibitors; Drug Therapy, Combination; Humans